Deployment of Sawdust as Substrate Medium in Hydroponically Grown Lettuce - Christoulaki, Marirena; Gouma, Sofia; Manios, Thrassyvoulos; Tzortzakis, Nikos G. (My University, 2014)
In this study, lettuce plants were grown in sawdust (Saw) and/or perlite (Per) mixtures (sawdust; Saw:Per 75:25%; Saw:Per 50:50%; Saw:Per 25:75%; Perlite) and in Nutrient Film Technique (NFT), in an unheated greenhouse. Plants grown in NFT were taller with greater leaf area resulting in greater fresh weight. Sawdust addition reduced leaf length, leaf area and as a consequence the fresh weight but not the leaf number. However, leaf dry weight increased as sawdust content increased into the substrate. Leaf chlorophyll reduced but leaf fluoresces increased in perlite and NFT. High sawdust content (75% or 100%) reduced photosynthetic rates and stomatal conductance. Nutrient uptake [potassium (K), sodium (Na), phosphorus (P)] was the greatest in NFT treatment, while perlite and Saw:Per 25:75% increased elemental uptake (up to 74%) comparing with the remaining treatments. Leaf elemental analysis fluctuated among treatments. Thus, low content (i.e. 25%) of sawdust in perlite could improve inorganic substrate media properties.
Keywords: Lactuca sativa; Sawdust; NFT; Organic materials; Perlite; Plant growth; Soilless culture; Lettuce; Yield